Jaunāko klašu skolēnu hiperaktīvas uzvedības iezīmes un to korekcija - Čirkova, Alla (Latvijas Universitāte, 2010)
Jaunāko klašu skolēnu hiperaktīvas uzvedības iezīmes un to korekcija

Characteristic features of hyperactive behaviour of the junior pupils and their correction
Characteristic features of hyperactive behaviour of the junior pupils and their correction
Keywords: Pedagoģija